(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2024)
This study was conducted to explore the role of envy on the psychological well-being of Instagram users. A total of 385 female Instagram users in the emerging adulthood stage (aged 18 to 24 years) participated in the study. Accidental sampling was used to collect data. The measuring instruments used in this study were developed based on the six dimensions of psychological well-being from Ryff and Singer (1996) and two core features of envy from Smith et al. (1999). The results of the study showed that there was a significant role of envy (inferiority and ill will features) on psychological well-being. In addition, the results of this study also showed that only two dimensions of psychological well-being could moderate envy, namely self-acceptance and autonomy.